The importance of multidisciplinarity in surgical and supportive conduct in severe odontogenic infection: Case Report (Research, Society and Development, 2021)
Odontogenic infections can evolve quickly and offer a high risk of death, since they are commonly associated with extensive tissue deterioration, in addition to their location, in close contact with important anatomical structures such as the airways, which can lead to their obstruction. The objective is to report, possible difficulties in the management of a patient, due to the Angina de Ludwig and consequent deviation of the airways, and the importance of the multidisciplinary medical-dental approach. Male patient, 33 years old, complaining of pain in the region of the lower right third molar, with evolution of one week, with extraoral edema that progressed gradually, was submitted to drainage still in the emergency, then the team proceeded with his hospitalization, the next day, the patient was taken to the operating room for further drainage, and extraction of dental elements associated with infection. At the time of intubation, there was difficulty due to the displacement of the tongue, which prevented adequate passage of the tube, directing the treatment to a tracheostomy. It is essential that the cause be removed, in order for it to regress and in view of the surgical need, it is essential that in the preoperative evaluation, the medical team evaluates possible airway compromises that may culminate in difficulties for intubation. There is no consensus about the approach for intubation in angina conditions due to a wide variety of situations, however, there is a need for a multidisciplinary medical-dental approach in order to achieve a fast and accurate approach.